Accelerated aging test in determining the vigour of sunflower seeds with and without pericarp - Ducatti, K. R.; Boeno, R. S.; Arantes, K. S.; Coimbra, R. A. (Scientific Electronic Archives, 2014)
The standard germination test alone is insufficient to attest the quality of seeds, making necessary correlationâ€™s with vigour tests, to determine more accurately the physiological potential of a seeds lot. The accelerated aging test is an option for determine the vigour and consists in submits seeds to high temperatures and humidity, for different periods of time, has not yet standardized.Â The objective of this workÂ was to analyze the efficiency of the accelerated aging test in the assessment of the effect of a lot of sunflower seed, by three periods of aging (48, 56 and 72 hours) in 42 Â°C temperature, in seeds with and without pericarp (manually removed) and relate the results with electrical conductivity test and germination first count. The experimental design was a completelyÂ randomized designÂ and the comparison of averagesÂ made using Tukey’s testÂ Â Â at 5% probability. The results showed that standard germination, electrical conductivity and germination first count, the seeds without pericarp showed better performance. In relation to the accelerated aging, only in the period of 72 hours of aging there was no significant difference between the treatments. In this way, the appropriate period to identify differences in force between the treatments was 72 hours, which showed a positive correlation with the germination first count and electrical conductivity. Â Keywords:Â Helianthus annuus, temperature, physiological potential, electrical conductivity.